The Effect of Competence on Performance with Self Confidence as an Intervening Variable - Munir, Syahrul (Prosiding Seminar, 2020)
This study aims to obtain empirical evidence about the effect of competence on employee performance with self-confidence as an intervening variable on the employees of Klinik Utama Rawat Inap Nuraini. The research method used is a survey method with quantitative research approaches. While the study used the SPSS 16.0 test technique. The results of this study are expected to provide input and suggestions that can be used in improving the performance of Clinic employees. It showed that employee competence significantly affected employee performance through self-confidence.